Diagenetic Quality, Extent of Alteration and Preservation of Organic Matter of Wells A and B in Niger Delta Basin, Nigeria - C. O. Igili; O. V. Ndubueze (Journal of Applied Sciences and Environmental Management)
This study investigates the application of palynofacies and calcareous nannofossils in determining the diagenetic qualities of Wells A and B in the Niger Delta Basin. The objective is to evaluate the diagenetic quality, extent of alteration and preservation of organic matter. The acid method for samples preparation was employed for the recovery of biofacies assemblages present in the two wells. The assemblages were dominated by moderate records of terrestrial sporomorphs such as Retitricolporites irregularis, Monocolpites sp., Laevigatosporites sp., Verrucatosporites sp., Acrostichum aureum, Psilatricolporites crassus and nannofossils such as Discoaster bollii, Discoaster, Catinaster coalitus, Reticulofenestra pseudoumbilicus, Sphenolithus moriformis, Coccolithus pelagicus and Helicosphaera carteri. Occurrence of Verrucatosporites sp., Acrostichum aureum, and Psilatricolporites crassus may indicate some degree of degradation or oxidation, suggesting fair preservation quality. These palynomorphs are more susceptible to degradation. Abundance of Botryococcus braunii, Echiperiporites estelae, and fungal spores could indicate shallow water environment with potential degradation or contamination, suggesting poor preservation quality. Presence of Reticulofenestra pseudoumbilicus and Sphenolithus moriformis may indicate some degree of dissolution, potentially related to changes in pH or oxygen levels. Abundance of Sphenolithus moriformis could suggest overcompaction, leading to deformation or fragmentation of nannofossils. Occurrence of Catinaster coalitus and Coccolithus pelagicus may indicate some degree of reworking, potentially due to changes in sediment supply or winnowing. In conclusion, the wells has experienced varying degrees of diagenetic alteration. While some intervals show good preservation quality, others have undergone oxidation, degradation, or contamination, resulting in fair to poor preservation quality. Also there is no significance difference between the two wells.